Parental Involvement Management In Enhancing The Quality Of Qur’anic Tahfidz Learning - Rohandi Yusup; Muh. Hanif (JIEMAN: Journal of Islamic Educational Management, 2025)
The objective of this study is to explore how the management of parental involvement contributes to enhancing the quality of Tahfidz Al-Qur'an instruction at MI Plus Ma’arif NU Makam, Purbalingga Regency. This study is based on the premise that synergy between families and educational institutions plays a vital role in shaping students’ character and academic success, especially within the realm of religious education. Employing a qualitative approach and a case study method, data were gathered through in-depth interviews, participatory observations, and document analysis involving the madrasah principal, teaching staff, and parents. The results demonstrate that parental involvement is managed across six fundamental dimensions: participatory planning, collaborative-based organising, structured program implementation, continuous evaluation, tangible parental contributions to students’ memorisation progress, and challenges in implementation.  Parental involvement in the Tahfidz program manifests across six managerial dimensions identified in this study. In participatory planning, parents contribute through curriculum review and target-setting discussions. Collaborative organising is reflected in the formation of program teams involving teachers, school leaders, and parent representatives. During implementation, parents support daily murojaah, utilise communication books, and participate in parenting and paguyuban activities. In control and evaluation, they engage in diagnostic, formative, and summative assessments. Parental contributions significantly enhance students’ memorisation progress through structured home routines and active communication with teachers. However, challenges include unequal participation levels, limited parental availability, and inconsistent documentation of supervision. These findings indicate the need for more inclusive and adaptive managerial strategies to strengthen school–family partnerships in Tahfidz learning.